Perlindungan Hukum Terhadap Nasabah Dalam Pelaksanaan Pinjam Meminjam Uang Berbasis Fintech - Aditya Sulistyo Budhi (Lembaga Pengembangan Kinerja Dosen, 2024)
In the digital era, technological developments are increasingly rapid, and their existence has begun to penetrate into various aspects of life, such as in the world of finance or the economy. This is marked by the emergence of technology and information-based financial institutions or known as fintech. Starting from this, a question arises on how to implement information technology-based lending and borrowing (peer to peer lending) in Indonesia and how to protect the recipients of the loan (customers). This research is in the form of juridical-normative. The results of this study concluded that there were violations committed by the lender to the customer, and the sanctions imposed were only administrative sanctions with the worst consequence being license revocation. In this regards, obviously it does not provide a sense of justice to the customers, considering the crimes that have been committed, therefore the role of criminal law is very important here, by implementing sanctions related to these crimes, such as the dissemination of personal data, threats in billing, sexual harassment through electronic media, fraud and slander.